From Pure Tones to Complex Sounds: Expanding Audiology Tools to Better Address Speech and Language Development - Binos, Paris; Korres, George; Papastefanou, Theodora; Papadimitriou, Nikolaos; Psillas, George K. (My University, 2024)
This editorial highlights the limitations of relying solely on pure-tone audiometry for diagnosing and managing hearing loss, particularly in the fields of speech-language pathology and audiology. While pure-tone audiometry has long been the gold standard for assessing hearing sensitivity, its capacity to fully capture the complexities of hearing impairments is increasingly called into question. The article examines the profound impact of hearing loss on language development, psychosocial well-being, and quality of life, especially in infants and toddlers, who are at risk of significant delays in speech and language development. These delays affect various linguistic domains, including morphology, vocabulary, syntax, semantics, and speech intelligibility. Hearing loss often distorts sound perception, particularly of softer consonants and key morphemes critical for understanding verb tenses, possessives, and plurals, further hindering language comprehension and communication. The article critiques traditional training programs for speech-language pathologists (SLPs) and audiologists, which tend to focus on basic pure-tone audiograms and standardized hearing loss classifications. It argues for a more comprehensive educational approach that emphasizes deeper audiogram interpretation, enabling improved diagnosis and management of hearing loss. Additionally, while remaining focused on pure-tone audiometry, the article discusses how SLPs can be better equipped to "decode" audiogram data, thereby enhancing early intervention strategies to support optimal language development in young children with hearing loss.
Keywords: audiogram; audiological tests; pediatric hearing loss; speech language pathology; speech perception